ETUDE DE LA QUALITÉ PHYSICO-CHIMIQUE ET CONTAMINATION MÉTALLIQUE DES EAUX DE SURFACE DU BASSIN VERSANT DE GUIGOU, MAROC - Akil, Abboudi; Hassan, Tabyaoui; Fatima, El Hamichi; Lahcen, Benaabidate; Abderrahim, Lahrach (European Scientific Journal, ESJ, 2014)
This study was carried out in November 2012 on the surface water of Oued Guigou. Samples have been analyzed according to the techniques for evaluation of water quality described by Rodier (2009) and the recommendations of the World Health Organization. This study concerns the analysis of physico-chemical parameters (T, pH, Electrical conductivity, SO4 2-, Cl-, NO2, NO3 -, Dissolved oxygen) and the assessment of contamination by trace elements (Fe, Pb, Cu, Zn, .. ) in order to characterize the quality of surface waters in Oued Guigou. The results of the physico-chemical analyzes show that the waters of this river are characterized by a low natural mineralization (430 μs/cm) and concentrations of less than the standards recommended by The WHO (1984) and Moroccan standards (MATEE, 2002) of the various parameters and also the concentrations too low see null in heavy metals which testify in general, that the waters of this watercourse is of a good quality.